1999
DOI: 10.1677/joe.0.163r011
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of leptin mRNA in fetal adipose tissue is related to fetal body weight

Abstract: Leptin mRNA was measured in adipose tissue of fetal sheep by reverse transcription polymerase chain reaction (RTPCR). Thus the leptin synthetic capacity of fetal adipose tissue appears to increase in late gestation but this is accompanied by constraint of its sensitivity to fetal body weight. We hypothesise that leptin synthesis in fetal adipose tissue is related to fetal nutrient supply and growth rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 29 publications
(10 reference statements)
2
59
0
Order By: Relevance
“…The increase in the abundance of LEP mRNA in intermuscular AT may reflect an enhanced ability to synthesize LEP, which could in turn sustain the increase in plasma LEP levels from 210 dpc onwards, at least in Charolais foetuses. In line with our results, an increase in LEP mRNA abundances in perirenal AT (Yuen et al, 1999) and plasma LEP (Yuen et al, 2003) was reported in ovine foetuses during the last month before birth.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in the abundance of LEP mRNA in intermuscular AT may reflect an enhanced ability to synthesize LEP, which could in turn sustain the increase in plasma LEP levels from 210 dpc onwards, at least in Charolais foetuses. In line with our results, an increase in LEP mRNA abundances in perirenal AT (Yuen et al, 1999) and plasma LEP (Yuen et al, 2003) was reported in ovine foetuses during the last month before birth.…”
Section: Discussionsupporting
confidence: 93%
“…The negative relationships between birthweight and subsequent leptin production in adulthood are the opposite of the reported positive correlations seen between body weight and leptin production in fetuses (21) and infants (11±14). Maternal nutrition during pregnancy in¯uences the body weight of the fetus (22±24) and, in female pigs, plasma leptin concentrations are higher in progeny from mothers provided with more feed (25).…”
Section: Introductionmentioning
confidence: 65%
“…In one study, fetal plasma leptin was positively correlated with plasma cortisol, but inversely correlated with PaO2 [31]. Fetal body weight was shown to be inversely related to plasma leptin concentrations in one study [32] but in another [33] body weight was positively correlated with leptin mRNA, which strongly correlates with plasma leptin [34]. We have not [12] and in 70-75 year old men and women [10].…”
Section: Body Compositionmentioning
confidence: 73%